Use of Gold Mine Waste Sand From Penda Pilang Village as Hrs-Base Mixture - Deskianto Deskianto; Supiyan Supiyan; Devia Devia (Universitas Insan Cendekia Mandiri, 2023)
Roads are very vital access or transportation infrastructure for human movement from one location to another. The materials utilized must fulfill the quality criteria established with respect for economics, availability of natural resources, and efficient distribution. This study used gold mine waste sand as a component of Hot Rolled Sheet Base. (HRS-BASE), this material has considerable potential that has not been utilized properly and is expected to be an alternative material in the area well as one of the steps to handle waste reduction by increasing its function value. Analyzing the characteristics of gold mine waste sand marshall with a composition of Optimum Asphalt Content (KAO) of 7% resulted in a stability value of 975.522 kg, flow of 3.10 mm, Inter-Aggregate Cavities (VMA) of 18.600%, Cavities in the Mixture (VIM) of 3.221%, Cavities Filled with Asphalt (VFB) of 82.689%, and Marshall Quotient of 314.712kg/mm.